Real-Time Audio Transformer Emulation for Virtual Tube Amplifiers. (22nd February 2011) - Cauduro Dias de Paiva Cauduro Dias de Paiva, Rafael Rafael; Pakarinen Pakarinen, Jyri Jyri; Välimäki Välimäki, Vesa Vesa; Tikander Tikander, Miikka Miikka
Abstract : An audio transformer is used in a guitar amplifier to match the impedances of the power amplifier and a loudspeaker. It is important to understand the influence of the audio transformer on the overall sound quality for realistic tube amplifier emulation. This paper proposes to simulate the audio transformer using a wave digital filter model, which is based on the gyrator-capacitor analogy. The proposed model is two-directional in the sense that it outputs the loudspeaker current, but it also connects backward to the power amplifier thus affecting its behavior in a nonlinear manner. A practical parameter estimation procedure is introduced, which requires only the measurement of basic electrical quantities but no knowledge of material properties. Measurements of a Fender NSC041318 and a Hammond T1750V transformer are presented as case studies, as well as parameter fitting and simulation for the Fender transformer. The results show that these practical transformer designs introduce distortion at low frequencies only, below about 100 Hz for the Fender and 30 Hz for the Hammond transformer, and that the proposed model faithfully reproduces this effect. The proposed audio transformer model is implemented in real time using the BlockCompiler software. Parametric control allows varying and also exaggerating the model nonlinearities.